Comprehensive Analysis of Inhibitor of Apoptosis Protein Expression and Prognostic Significance in Non–Small Cell Lung Cancer - Liu, Jun; Lu, Yi; Huang, Wenan; He, Zhibo (Frontiers in Genetics, 2021)
Inhibitor of apoptosis proteins (IAPs) has been associated with tumor development and progression by affecting apoptosis through cell death signaling pathways. To date, eight IAPs (BIRC1–8) have been identified in mammalian cells. However, the role of IAPs in non-small lung cancer (NSCLC) development and progression has not been explored in depth. In this study, we used public datasets and bioinformatics tools to compare the expression, prognostic significance, and function of IAPs in NSCLC and its subtypes. Expression of IAPs in cancer and normal tissues and at different stages of NSCLC was compared with gene expression profiling interactive analysis, and their prognostic significance was analyzed with the Kaplan-Meier Plotter database. The correlations among IAPs were analyzed with the STRING database and SPSS19.0. Functional annotation of IAPs was analyzed by Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment based on the DAVID tool. Among patients with lung adenocarcinoma (LUAD), the expression level of BIRC5 was higher than that in normal samples and the expression of BIRC1 and BIRC5 significantly varied in different stages. Moreover, the BIRC1–3 and BIRC5 mRNA levels were associated with overall survival (OS), and the BIRC1–2 and BIRC5–6 mRNA levels were associated with progression-free survival (PFS). Among patients with lung squamous cell carcinoma (LUSC), the expression level of BIRC1 was lower and that of BIRC5 was higher than those in normal tissues, and BIRC5 expression significantly varied in different stages. BIRC1 expression was associated with OS, whereas BIRC2 and BIRC6 expression was associated with PFS. Enrichment analysis showed that most IAPs are associated with ubiquitin- and apoptosis-related pathways. Collectively, this study suggests BIRC5 as a potential diagnostic and staging marker, BIRC1 as a potential marker of OS, and BIRC2 and BIRC6 as potential PFS markers for patients with NSCLC. These highlight new targets for the early detection, treatment, and management of NSCLC.